Influence of the input and iteraction on vocabulary acquisition in the tenth year at "Ciudad de Cuenca" High School During the second period of the school year 2014-2015 - Correa Moncayo, Liliana Teresa (2015)
The present research aims to investigate whether it is possible to acquire English vocabulary in a classroom situation without resorting to direct instruction. This assumption is based on the principles of two prominent theories: Input Hypothesis and Interaction hypothesis. Participants were 76 students in the "Ciudad de Cuenca" High School in their tenth year. Two intact classes serving as a control group and an experimental group respectively were involved in this study. The control group followed regular instruction as determined by the State school curriculum and programs, while the experimental group received permanent target language input and was given the opportunity to interact. This involves extensive use of English by the teacher during English classes.